The Izala Movement in Nigeria Genesis, Fragmentation and Revival - Ben Amara, Ramzi (Universitätsverlag Göttingen, 2020)
On the basis on solid fieldwork in northern Nigeria including participant observation, interviews with Izala, Sufis, and religion experts, and collection of unpublished material related to Izala, three aspects of the development of Izala past and present are analysed: its split, its relationship to Sufis, and its perception of sharīʿa re-implementation. "Field Theory" of Pierre Bourdieu, "Religious Market Theory" of Rodney Start, and "Modes of Religiosity Theory" of Harvey Whitehouse are theoretical tools of understanding the religious landscape of northern Nigeria and the dynamics of Islamic movements and groups.